EARNINGS MANAGEMENT, BANK’S MANAGERS COMPENSATION, AND FACTORS THAT INFLUENCE THE COMPENSATION: AN INDONESIAN CASE - Rahmat Febrianto; Erna Widiastuty; Etik Kresnawati (SRIWIJAYA INTERNATIONAL JOURNAL OF DYNAMIC ECONOMICS AND BUSINESS, 2022)
This study is motivated by the enactment of Indonesian Financial Service Authority (FSA) regulation. This regulation requires bank to implement remuneration scheme to their employee. It specifies that bank must have a plan to holdback or clawback the variable remuneration, to protect bank from imprudent risk taking.Our research has two objectives. First, this study is to detect post-implementation earnings management. Second, we determine factors that influence banks to choose clawback. Samples are all banks listed at the Indonesian Stock Exchange and are divided into two periods: pre- and post-regulation.The tests results indicate that banks manage their earnings after the adoption of the regulation. The second test result presents that earnings before tax, equity, and non-performing loans have a positive and statistically significant relationship with the banks intention to choose clawback. We also report some implications, limitations, and future research opportunities.